Acute pulmonary embolism following dual-chamber pacemaker implantation: a case report - Song, Zhizhou; Zhang, Yanhua; Wang, Yanan; Hao, Lijuan; Ma, Ying; Liu, Qiang; Wu, Qi; Huo, Yuehong (Frontiers in Cardiovascular Medicine, 2025)
Acute pulmonary embolism (APE), a critical complication following permanent pacemaker implantation, presents profound therapeutic challenges when occurring during the early postoperative phase. We report a 73-year-old female who developed high-risk APE with cardiogenic shock 47 h after dual-chamber pacemaker implantation via the right subclavian vein. The immobilization of the affected upper limb and bed rest, along with endothelial injury during the implantation process, can trigger an inflammatory response and activate the coagulation cascade, ultimately leading to a pro-coagulant state, which may subsequently induce deep vein thrombosis in the lower extremities and subsequent bilateral pulmonary embolism. Following the 2019 ESC guidelines for managing high-risk APE, prompt intravenous thrombolysis with alteplase (50 mg) stabilized hemodynamics. However, this intervention caused pacemaker pocket hemorrhage. Strategic intermittent elastic compression bandaging mitigated hematoma progression without compromising wound healing. Anticoagulation with warfarin (INR 2–3) and serial imaging confirmed resolution of thromboembolic burden and right atrial remodeling. This case underscores the delicate balance between life-saving reperfusion and device-related complications in pacemaker recipients, advocating for tailored hemostatic strategies in high-risk cohorts.